Assessing Uranium Ore Processing Activities Using Satellite Imagery at Pyongsan in the Democratic People's Republic of Korea. Issue 3 (2nd September 2021) - Park, Sulgiye; Terry McNulty,; Puccioni, Allison; Ewing, Rodney C.
Abstract: The Democratic People's Republic of Korea (DPRK)'s only confirmed uranium mill is within the Pyongsan uranium mining complex. The ore processing pathway and the production capacity for uranium concentrate is analyzed, based on comprehensive satellite imagery analysis of this facility. This assessment of the Pyongsan facility indicates an ore processing capacity of ∼750–1, 200 tonnes per day. One year of maximum production at Pyongsan would yield enough processed ore to fuel one load of the 5 MWe reactor in Yongbyon as well as ∼3, 000 kg of LEU or ∼100 kg of HEU. The analysis suggests that the ore processing capacity at Pyongsan is not a constraint on the DPRK's nuclear material production and that the available capacity at the Pyongsan milling facility strongly suggests that the DPRK has no need in another uranium milling facility of a comparable size. This report provides an improved understanding of the ore processing steps and production rates of the only confirmed uranium mill in the DPRK, enabling a more quantitative assessment of its nuclear materials production and inventories.